Political Anthropology Seen Through Populism and Apocalyptic Imaginaries - Fridlund, Patrik ; 0000-0003-0067-0584 (Eco-Ethica, 2026)
One characteristic trait of populism is its dramatic rhetoric on themes such as the survival of the European people. This is particularly present in a cluster of conspiracy theories, in this article discussed under the collective term le grand remplacement, forming a cornerstone of much right-wing populist rhetoric. In this article, it is suggested that the notion of “apocalyptic imaginaries” is a helpful tool in the process of observing, classifying, and eventually understanding this kind of populism and its political anthropology. If populism is read through the lens of apocalyptic imaginaries, it brings “political rationality” into perspective, as “the rational” is not always held to be important in political rhetoric. Moreover, “the rational” is not self-evident, and political discourses must not be discarded just because they appear to be paradoxical or ambivalent.
Keywords: right-wing populism; apocalyptic imaginaries; le grand rem- placement; Eurabia; revealed knowledge